The Role of Blockchain Technology and Financial Literacy in Shaping Cryptocurrency Investment Decisions - Ahmad Gunawan; Hilda; Oscar Jayanegara; Rion Wang (IAIC Bangun Bangsa, 2025)
The rapid growth of cryptocurrency markets has raised important questions about how investors make decisions in this highly volatile space. This research investigates the role of blockchain technology and financial literacy in shaping cryptocurrency investment decisions, focusing on how these factors influence investor behavior and risk management. The study aims to explore how blockchain’s decentralized nature provides security and transparency in cryptocurrency transactions and how a higher level of financial literacy can improve decision making among investors. A mixed-method approach was used, combining a quantitative survey of 300 cryptocurrency investors with qualitative interviews from 15 experienced market participants. The survey assessed financial literacy levels, understanding of blockchain technology, and investment decision-making, while the interviews provided deeper insights into how these factors interconnect. The findings indicate that blockchain technology perceived security and transparency significantly enhance investor confidence, while higher financial literacy levels correlate with more informed and strategic investment decisions. Furthermore, investors with both high blockchain knowledge and financial literacy are better at managing risk and avoiding common pitfalls in the market. The study concludes that both blockchain technology and financial literacy are crucial in shaping effective cryptocurrency investment strategies. Policymakers and financial educators should focus on improving fi- nancial literacy to empower investors and ensure better market stability. This research provides valuable insights for the development of educational frame- works and policies to support informed decision-making in cryptocurrency investments.